Tembang Batanghari Sembilan and Character Building - Yanti Sariasih; Fathiaty Murthado; Zainal Rafli (Edunesia: Jurnal Ilmiah Pendidikan, 2021)
This paper begins with a concern over the existence of regional oral literature which is increasingly "isolated" from the hustle and bustle of the modern world today. The lack of efforts to preserve oral literature, which is actually an asset of the community itself, and there are not many generations who want to cultivate this oral literature as a form of cultural responsibility for their society. It is feared that this will backfire for oral literature so that one day this oral literature will disappear. In this paper, the author tries to reveal and describe the cultural values ​​contained in the Tembang Batanghari Sembilan (TBS) by using content analysis research methods and ethnographic analysis. The results of this study reveal that the TBS contains character education that has been maintained until now through development and cultural activities that exist in the Semende community in Ogan Komering Ulu Selatan (OKUS) regency